Stages of Grief Portrayed on the Internet: A Systematic Analysis and Critical Appraisal - Avis, Kate Anne; Stroebe, Margaret; Schut, Henk (Frontiers in Psychology, 2021)
Kübler-Ross’s stage model of grief, while still extremely popular and frequently-accepted, has also elicited significant criticisms against its adoption as a guideline for grieving. Inaccurate portrayal of the model may lead to bereaved individuals feeling that they are grieving incorrectly. This may also result in ineffectual support from loved ones and healthcare professionals. These harmful consequences make the presentation of the five stages model an important area of concern. The Internet provides ample resources for accessing information about grief, raising questions about portrayal of the stages model on digital resources. We therefore conducted a systematic narrative review using Google to examine how Kübler-Ross’s five stages model is presented on the internet. We specifically examined the prominence of the model, whether warnings, limitations and criticisms are provided, and how positively the model is endorsed. 72 websites were eligible for inclusion in the sample. Our analyses showed that 44 of these (61.1 %) addressed the model, indicating its continued popularity. Evaluation scores were calculated to provide quantitative assessments of the extent to which the websites criticized and/or endorsed the model. Results indicated low criticalness of the model, with sites often neglecting evaluative commentary and including definitive statements of endorsement. We conclude that such presentation is misleading; a definitive and uncritical portrayal of the model may give the impression that experiencing the stages is the only way to grieve. This may have harmful consequences for bereaved persons. It may alienate those who do not relate to the model. Presentation of the model should be limited to acknowledging its historical significance, should include critical appraisal, and present contemporary alternative models which better-represent processes of grief and grieving.